Clinical characteristics and outcomes among older nursing home residents hospitalized with pneumonia. (July 2021) - Kim, Nam Eun; Lee, Jin Hwa; Chang, Jung Hyun; Lee, Su Hwan; Ryu, Yon Ju
Highlights: A high proportion of cases of nursing home-acquired pneumonia are caused by multidrug-resistant pathogens. The presence of a multidrug-resistant pathogen is an independent risk factor for mortality due to the limited options for antibiotic therapy. Newly approved antibiotics which have broad spectrum activity against MDR pathogens would be an effective therapeutic option. Abstract: Background: : Due to population aging, the number of cases of pneumonia in nursing homes in South Korea has been increasing. This study investigated the characteristics and clinical outcomes in nursing home residents with pneumonia admitted to a tertiary hospital. Methods: : A retrospective cohort study was conducted of patients transferred to the tertiary hospital from nursing homes between August 2009 and October 2016. The in-hospital mortality, Pneumonia Severity Index, bacterial pathogens in sputum cultures, and antibiotic sensitivity profile were assessed. Results: : The analysis included a total of 174 patients hospitalized with pneumonia. Their median age was 78 years, and 109 patients (62.6%) were male. 108 patients (62.1%) were admitted to the intensive care unit. The in-hospital mortality rate was 12.6% (22/174). Culture of a multidrug-resistant (MDR) pathogen was an independent risk factor for mortality (odds ratio [OR]: 3.72, 95% confidence interval [CI]: 1.16–11.89). Male sex and a history of antibiotic use within the previous 3 months were independent risk factors for MDR pathogen isolation (OR: 3.32, 95% CI, 1.38–7.98 and OR: 3.93, 95% CI: 1.82–8.49, respectively). Conclusions: : Detection of an MDR pathogen, rather than host factors such as old age, bedridden status, and comorbidities, was the most important risk factor for in-hospital mortality in patients with nursing home pneumonia. Patients with a history of antibiotic use within the previous 3 months had a higher probability of MDR pathogen identification. Identifying MDR pathogens is important in treating older nursing home residents with pneumonia.